Magnetic Anisotropy Dominates over Physical and Magnetic Structure in Performance of Magnetic Nanoflowers - Julie Borchers; Kathryn Krycka; Brianna Bosch‐Santos; Eduardo de Lima Correa; Anirudh Sharma; Hayden Carlton; Yanliu Dang; Michael Donahue; Cordula Grüttner; Robert Ivkov; Cindi L. Dennis (Small Structures)
Magnetic nanoparticles are indispensable in many biomedical applications, but it remains unclear how the composition and structure will influence the application specific performance. We consider two compositions, ferrite and cobalt ferrite, synthesized under conditions that create aggregated multi‐core nanoparticles, called nanoflowers. Each nanoflower has an ionic surfactant or dextran to provide colloid stability in water. The composition, but not the coating, greatly impacts the heating output and the magnetic particle imaging tracer quality (with cobalt ferrite significantly reduced compared to ferrite). The cobalt ferrite nanoflowers have a core/shell structure with a reduced magnetization, which limits the effective magnetic anisotropy of the individual cobalt ferrite nanoflowers as well as the magnetic interactions among the nanoflowers. Both limitations significantly reduce the overall increase in the magnetic anisotropy with increasing magnetic field and consequently the nanoflowers’ efficacy for heating and imaging. Despite this, the formation of denser‐packed clusters and chains with external magnetic field in the ionic surfactant‐cobalt ferrite nanoflowers overcomes some of the shell's detrimental effects, resulting in better heating and imaging properties compared to the dextran‐cobalt ferrite. In short, the magnetic anisotropy dominates over physical and magnetic structure in the performance of the studied nanoflowers for heating and imaging applications.